Adaptive Collaboration Governance: A Sociological–Economic Study of Outliers, Communication Quality, and Partnership Sustainability - Edwin Lumunon; Juliet Makinggung; Jemmry Winokan; Rolyke Tulangow (Universitas Pattimura, 2026)
This study aims to analyze the effectiveness of collaboration governance between higher education institutions and external partners by highlighting the role of outliers, communication quality, and partnership sustainability within a socio-economic framework. Using an explanatory quantitative design, data from 100 collaboration projects across five Indonesian universities were processed with SPSS 26 through data cleaning, normality testing, outlier detection using scatter and box plots, Pearson correlations, and multiple linear regression to examine the influence of communication intensity, funding effectiveness, and partner satisfaction on sustainability. The findings show that communication quality significantly enhances partner satisfaction, which emerges as the strongest predictor of sustained partnerships, while meeting frequency and funding size do not consistently translate into improved outcomes due to diminishing returns and administratively driven communication. Negative outliers serve as early indicators of potential failure, whereas positive outliers reveal efficient collaborative practices that can be replicated. The study’s novelty lies in proposing the concept of adaptive collaboration governance, which integrates socio-economic theory with outlier analysis as an empirical diagnostic tool for understanding relational dynamics. The study contributes to the advancement of sociological economics and organizational sociology by demonstrating the value of evidence-based approaches that combine statistical analysis with relational interpretation to strengthen institutional collaboration and long-term partnership sustainability.